The Effect of SETS Based Problem Based Learning on Student's Creative Thinking Ability - Ahmad Adil; Syahrianti Syam; Muhammad Safar; Christanso Syam; Tri Satriawansyah; Rusmawan Rusmawan (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of the size of the influence of the SETS-based Problem Based Learning (PBL) model on students' creative thinking ability. This research is Quantitative research with meta-analysis method. Data sources come from national and international journals. The inclusion criteria in the research are research obtained through the google Scholar, IEEE, ERIC, ScienceDirect and ProQuest databases, research published in 2019-2023, research indexed by SINTA, Web of Science (WOS), and Scopus, Research related to Sports and Health Physical Education subjects, Research must have experimental classes with SETS-based Problem Based Learning models and conventional control model classes,Â  and the study must have a sample size(N), Mean, and Standard deviation (SD). Data analysis in this study with the JSAP application. The results of the analysis of 18 studies concluded that there was a positive influence of the SETS-based Problem Based Learning model on students' creative thinking ability (rE = 0.848; Z = 5.109; p < 0.001). This finding explains that the SETS-based Problem Based Learning model has a high influence on students' creative thinking skills in learning Physical Education, Sports and Health